(untitled) (Al-NASR, 2024)
This article examines the personality development aspect from an Islamic perspective. Drawing on Islamic teachings and principles, it examines how morality, social interactions, and faith shape an individual’s character. The article examines how virtues that align with Islamic teachings can be developed through prayer, moral behavior, and community service. By combining psychological concepts with Islamic philosophy, this article aims to offer insights into an all-encompassing approach to personality development within an Islamic framework. Some theorists contend that religion provides the most complete framework for values and that religious orientations fall under an extrinsic category.